Further investigation of particle reinforced aluminum matrix composites by indentation experiments. Issue 4 (28th February 2014) - Yuan, Zhanwei; Li, Fuguo; Chen, Bo; Xue, Fengmei; Hussain, Mirza Zahid
Abstract